Management of Ectopic Pregnancies at the Community University Hospital Center (CUHC) in Bangui, Central African Republic - Thibaut Boris Clavaire Songo-Kette Gbekere; Alida Koirokpi; Rose de Lima Kogboma Wongo; Candy Marie Paule Serdouma; Severin Saturnin Heya Imbatia; Norbert Richard Ngbale; Abdoulaye Sepou (European Scientific Journal, ESJ, 2024)
Introduction: Ectopic pregnancy (EP) is an obstetrical emergency that affects women in the first trimester of pregnancy. We decided to find out more about the care of these women. Methodology: This was a cross-sectional study over a period of 6 months, from  November 1st, 2022 to  April 29th, 2023, covering both operated patients and medically treated for EP at the Community University Hospital Center (CUHC). Results: During this period, we recorded 103 cases of ectopic pregnancy out of 1659 deliveries,  representing a frequency of 6.2%. Patients under 35 years old were the most represented (88.3%). The majority of our patients had reached secondary school (54.4%) and were multiparous (33%). The gestational age of 8 – 12 weeks was the most affected during the consultation. Conclusion: Radical surgery remains the most used therapeutic method with 84.2% of cases in our study. Ectopic pregnancy is an extreme obstetrical emergency of the first trimester that requires adequate care. The best treatment is primary prevention by avoiding risk factors.